Achieving impactful treatment for paediatric endocrine disorders in low- to middle-income countries (LMICs): a scoping review - Carrie Dolan; Hannah Elise Olson (BMJ Open)
Objectives Endocrine disorders, such as hypo/hyperthyroidism and diabetes, affect over 5% of the world’s population, with an additional 5% of cases remaining undiagnosed. Despite the increasing prevalence of endocrine disorders, especially in low- to middle-income countries (LMICs), limited research offers comprehensive guidance on treating this complex medical field. This scoping review aims to provide evidence-based recommendations for efficient, effective and accessible treatment of paediatric thyroid conditions and diabetes in LMICs.Design Scoping review guidelines outlined by the Preferred Reporting Items for Systematic and Meta-Analysis Extension for Scoping Reviews, using the Joanna Briggs Institute (JBI) methodology to analyse healthcare administration approaches in LMICs.Data sources PubMed, Google Scholar, MEDLINE, EconLit, Science Direct and Scopus were searched using a set of search terms from 19 December 2023 to 16 January 2024. An additional high-level search was performed in May 2025.Eligibility criteria Selection of a variety of peer-reviewed publications with a setting in LMICs. Articles were included if they described an intervention strategy related to select paediatric chronic diseases, endocrine conditions or non-communicable diseases. The treatment strategies in question were government initiatives, mobile health, specialised programmes and primary care.Data extraction and synthesis One reviewer manually reviewed articles and documented findings on Microsoft Excel. In accordance with JBI methodological guidelines, no risk of bias assessment or quality appraisal of included studies was conducted.Results After reviewing primary care, specialised care, government intervention programmes and mobile care initiatives within developing countries, primary care with an emphasis on task shifting emerged as the best approach for treating paediatric endocrine disorders.Conclusion Despite recommendations favouring specialised care or government interventions, primary care proves to be the optimal method for treating endocrine conditions. Given limited healthcare funding in LMICs, implementing primary care initiatives can achieve significant health outcomes while maximising resources.